Pengaruh Bunga Deposito, Kurs Mata Uang, dan Harga Emas terhadap Indeks Harga Saham Gabungan (Ihsg) - Guntur Irianto (The Winners, 2002)
Article explores the effects of rate, rupiah, and US dollar kurs, and gold price to the IHSG by using a linier double regression model. It is concluded that deposit rate, rupiah and US dollar have a significant negatif effect to IHSG. Those two variables have interrelated substations to the exchange; otherwise the gold price had a posite effect to IHSG (EH).